Digital Contingency Management in the Treatment of Substance Use Disorders. (March 2023) - Dallery, Jesse; Defulio, Anthony; Raiff, Bethany R.
Contingency management (CM) provides incentives based on drug abstinence or other treatment goals; it is one of the most efficacious and cost-effective psychosocial interventions for substance use disorders. However, CM remains severely underused in clinical care. Digital methods to deliver CM could dramatically expand access. These methods include information and drug sensing technologies to obtain objective evidence of drug abstinence, authenticate the end-user's identity, and deliver incentives immediately. Digital CM has been applied successfully to cigarette smoking, alcohol misuse, and more recently illicit drug use. Policies should continue to evolve to promote the delivery of digital CM based on decades of research.